A 526 mJ Subnanosecond Pulsed Hybrid-Pumped Nd:YAG Laser. (July 2017) - Shi 石, Jiang-Peng 江鹏; Xin 辛, Jian-Guo 建国; Liu 刘, Jun 军; Chen 陈, Jia-Bin 家斌; Zaman, Sher
Abstract : A hybrid-pumped Nd:YAG pulse laser with a double-pass two-rod configuration is presented. The focal length of offset lens is particularly studied to compensate for the thermal lens effect and depolarization. For input pulse energy of 141 μJ with pulse duration of 754 ps, the pulse laser system delivers 526 mJ pulse energy and 728 ps pulse width output at 10 Hz with pulse profile shape preservation. The energy stability of the laser pulse is less than 3%, and the beam quality factor M 2 is less than 2.26.